INFORMATION TECHNOLOGY FOR SYNTHESIS OF GROUP DECISION MAKING METHODS - Mironova, N. A. (Radio Electronics, Computer Science, Control, 2013)
In the paper the problem of the mechanism of implementation of new methods for group decision making is solved in the form of information technology for synthesis of group decision-making methods. The study offers the information technology which allows the synthesis of variants of group decision-making methods depending on a set of input data. Also, formalization of phases is carried out in the study and block diagram describing the interaction of the basic elements of the technology is offered. In addition, the information technology for synthesis of group decision making methods is developed. It is based on the methodsadapters permitting to combine variety of methods with different functionalities. The information technology which contains a tool for synthesis of group decision-making methods is implemented and used to solve the important functional problem of simulation of the synthesis of a new group decision making method for group decision supporting systems.